The Study of Spray-Freeze-Drying Technique for Development of Novel Combination pMDIs, Part I: Study on the Preparation Method - Xi, Quan; Miao, Jia-Ying; Cao, Zhen; Wang, Hao (Pharmaceutical Fronts, 2022)
Clinically available pressurized metered-dose inhalers (pMDIs) mainly directly use micronized drugs as inhalable microparticles. Although technology for preparing pMDIs has proven to obtain clinically appropriate aerosol performance, the fine particle fraction and delivered dose content uniformity (DDCU) of pMDIs still need to be improved. DDCU problem is usually exacerbated by patients' handling errors prior to taking a dose. In this study, novel phospholipid microparticle inhalation pMDIs were prepared by a spray-freeze-drying process using mometasone furoate and formoterol fumarate dihydrate as model drugs and distearoylphosphatidylcholine as an excipient. Combined with the material composition, the atomization and freeze-drying processes were also studied. Our data showed that both atomization parameters of gas–liquid ratio and freeze-drying curve settings met the requirements of drug design. According to aerodynamic performance in vitro and DDCU evaluation, the performance of the phospholipid microparticle inhalation pMDI was better than that of the micronized drug microparticle pMDI. In conclusion, preparing pMDIs with particle engineering has the potential to ensure accuracy of quantification and to improve the efficiency of drug deposition in lungs in clinical practice.
Keywords: spray-freeze-drying; inhalable microparticles; pMDIs; phospholipids